2008
DOI: 10.1074/jbc.c800128200
|View full text |Cite
|
Sign up to set email alerts
|

c-IAP1 and c-IAP2 Are Critical Mediators of Tumor Necrosis Factor α (TNFα)-induced NF-κB Activation

Abstract: Cellular IAP12 and IAP2 (c-IAP1 and c-IAP2) were identified in a search for proteins associated with TNF receptors (TNFRs) (1). Through binding to TNFR-associated factor 2 (TRAF2), c-IAP1 and c-IAP2 are recruited to TNFR signaling complexes, where they regulate the activation of caspase-8 (1, 2). c-IAP1 and c-IAP2 were also proposed to modulate activation of the canonical NF-B pathway, although most of these studies relied on overexpression (3, 4). In contrast, however, targeted deletion of c-IAP1 or c-IAP2 ge… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

23
470
1
3

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 499 publications
(497 citation statements)
references
References 36 publications
23
470
1
3
Order By: Relevance
“…35,36,44 This conclusion is supported by the following lines of evidence: First, the TNFacatching antibody Enbrel fails to prevent BV6-induced cell death in primary CLL cells. Similarly, we recently described that BV6/Dexamethasone-induced cell death in childhood ALL occurs in a TNFa-independent manner.…”
Section: Discussionmentioning
confidence: 78%
“…35,36,44 This conclusion is supported by the following lines of evidence: First, the TNFacatching antibody Enbrel fails to prevent BV6-induced cell death in primary CLL cells. Similarly, we recently described that BV6/Dexamethasone-induced cell death in childhood ALL occurs in a TNFa-independent manner.…”
Section: Discussionmentioning
confidence: 78%
“…39 In contrast, the absence of both cIAP1 and cIAP2 is required for complete inhibition of TNFα-mediated survival, suggesting that these inhibitors have redundant functions. 20,21 Evidence also supports that cIAP2 has independent roles from cIAP1 in suppressing apoptosis. For examples, we and others have found that the levels of cIAP2, but not cIAP1, are greatly increased after TNFα stimulation.…”
Section: Discussionmentioning
confidence: 89%
“…18,19 Because cIAP1 and cIAP2 show functional redundancy in TNFα-mediated survival, the depletion of both proteins is usually required for effective induction of cell death upon TNFα treatment. 20,21 However, there are several reports showing that cIAP2 expression, but not cIAP1 expression, renders cells resistant to Smac mimetic-induced cell death. 20,21 For example, cIAP2 upregulation via phosphoinositide 3-kinase (PI3K) upon compound 3 treatment in certain cell lines was shown to facilitate apoptosis evasion.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This is followed by the recruitment of a number of E3 ubiquitin ligases to RIP1, including TNF receptor-associated factor 2 (TRAF2) or TRAF5 and the cellular inhibitor of apoptosis proteins (cIAPs) cIAP1 and cIAP2 resulting in the formation of Complex I. [21][22][23][24] TRAF2 25,26 and cIAPs [27][28][29][30] catalyse the polyubiquitination of RIP1. The ubiquitin-decorated RIP1 is recognized by ubiquitin-binding domain containing proteins in the IkB kinase (IKK) 31 and TAK1 kinase complexes [32][33][34] thus facilitating TAK-1-mediated phosphorylation and activation of IKKs.…”
Section: Rip1 and Tnf Signalling: Inflammation Versus Apoptosismentioning
confidence: 99%